2015
DOI: 10.1016/j.cmi.2014.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Collateral damage from oral ciprofloxacin versus nitrofurantoin in outpatients with urinary tract infections: a culture-free analysis of gut microbiota

Abstract: Recent treatment guidelines for uncomplicated urinary tract infections (UTIs) discourage fluoroquinolone prescription because of collateral damage to commensal microbiota, but the ecologic impact of alternative agents has not been evaluated by culture-free techniques. We prospectively collected faecal samples at three time points from ambulatory patients with UTIs treated with ciprofloxacin or nitrofurantoin, patients not requiring antibiotics and household contacts of ciprofloxacin-treated patients. We descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(79 citation statements)
references
References 37 publications
4
73
0
2
Order By: Relevance
“…Certain members of the genus Anaerovibrio are able to utilise glycerol24 and have been associated with propionate and butyrate production in the rumen2425. Previous studies revealed that squid ink polysaccharide and ciprofloxacin treatment were correlated with a reduced proportion of the genus Oscillospira in the gut2627. Hence, rumen concentrations of propionate and butyrate may be increased by feeding dairy calves UWM.…”
Section: Discussionmentioning
confidence: 99%
“…Certain members of the genus Anaerovibrio are able to utilise glycerol24 and have been associated with propionate and butyrate production in the rumen2425. Previous studies revealed that squid ink polysaccharide and ciprofloxacin treatment were correlated with a reduced proportion of the genus Oscillospira in the gut2627. Hence, rumen concentrations of propionate and butyrate may be increased by feeding dairy calves UWM.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a culture-based analysis revealed that oral administration of ciprofloxacin decreases the rate of ethanol elimination in humans16, probably because this drug reduces the proportions of aerobes and facultative anaerobes in the human intestine16. However, in recent culture-free GM analysis, ciprofloxacin administration to human subjects (outpatients with urinary tract infections) decreased the relative abundances of various obligate anaerobes, including Bifidobacterium and Ruminococcus 45. Thus, ciprofloxacin adversely affects not only aerobes and facultative anaerobes, but also obligate anaerobes.…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis is commonly characterized by a reduced diversity of the phyla Firmicutes and Bacteroidetes, and often accompanied by an overgrowth of the family Enterobacteriaceae [12,13,22,23,24,25]. This may become critical, as the healthy microbiota conveys colonization resistance towards invading pathogenic bacteria [26], and dysbiosis increases vulnerability for post-antibiotic expansion of enteropathogenic strains like Clostridium difficile [27] and antibiotic-resistant pathogens such as vancomycin-resistant Enterococcus [28].…”
Section: General Consequences Of Antibiotic Use On Gut Microbiota Commentioning
confidence: 99%